Development of a Subcutaneous Formulation for Trastuzumab – Nonclinical and Clinical Bridging Approach to the Approved Intravenous Dosing Regimen - Bittner, B.; Richter, W. F.; Hourcade-Potelleret, F.; McIntyre, C.; Herting, F.; Zepeda, M. L.; Schmidt, J. (Arzneimittelforschung, 2012)
A subcutaneous (SC) formulation has been developed for the humanized monoclonal antibody (mAb) trastuzumab as an alternative to established intravenous (IV) infusion. The ready-to-use liquid SC formulation is injected as a fixed dose in approximately 5 min, which is expected to increase patient’s convenience, reduce pharmacy preparation time, and administration costs overall.The trastuzumab dose as well as the dose of recombinant human hyaluronidase (rHuPH20), an enzyme that enables SC administration of volumes larger than 2 mL, was selected based on nonclinical xenograft, pharmacology, and pharmacokinetics mouse and minipig studies.The basic assumption for bridging from the IV to the SC regimen was that comparable trastuzumab serum trough concentrations would result in comparable efficacy. This hypothesis is confirmed by the results from the Phase 3 study in the neo-adjuvant/adjuvant setting. The safety profiles of the trastuzumab SC and IV formulations are comparable and consistent with the known safety profile of trastuzumab.
Keywords: subcutaneous; trastuzumab; injection device; dose finding; nonclinical; clinical